Răspuns :
a+b=49
b=a/2+13
a+ a/2+13=49
a+a/2=49-13
a+a/2=36⇒2a+a=36×2⇒3a=72⇒a=24
b=a/2+13=12+13=25
a=24 si b=25
verificare
a+b=49
24+25=49
b=a/2+13
a+ a/2+13=49
a+a/2=49-13
a+a/2=36⇒2a+a=36×2⇒3a=72⇒a=24
b=a/2+13=12+13=25
a=24 si b=25
verificare
a+b=49
24+25=49
a+b=49
a:2<b+13
--------------
a=?;b=?
2a=(49-13):3
2a=36:3
2a=12
a=12*2
a=24
b=(a:2)+13
b=(24:2)+13
b=12+13
b=25
a:2<b+13
24:2<12+13
12<25
25-12=13 (dif.dintre jumatatea lui "a" si rezultatul lui"b"
a+b=49
24+25=49
a:2<b+13
--------------
a=?;b=?
2a=(49-13):3
2a=36:3
2a=12
a=12*2
a=24
b=(a:2)+13
b=(24:2)+13
b=12+13
b=25
a:2<b+13
24:2<12+13
12<25
25-12=13 (dif.dintre jumatatea lui "a" si rezultatul lui"b"
a+b=49
24+25=49